Bulletin - Carlisle Industrial Crisis Committee, 8 May 1926 (Carlisle)
1926-05-08 "Bulletin - Carlisle Industrial Crisis Committee, 8 May 1926" [g0076001.jpg], 8 May 1926, Carlisle Industrial Crisis Committee Local Organisation